Dual role of protein kinase C on BK channel regulation - Zhou, Xiao-Bo; Wulfsen, Iris; Utku, Emine; Sausbier, Ulrike; Sausbier, Matthias; Wieland, Thomas; Ruth, Peter; Korth, Michael (Proceedings of the National Academy of Sciences of the United States of America, 2010)
Large conductance voltage- and Ca2+-activated potassium channels (BK channels) are important feedback regulators in excitable cells and are potently regulated by protein kinases. The present study reveals a dual role of protein kinase C (PKC) on BK channel regulation. Phosphorylation of S695 by PKC, located between the two regulators of K+ conductance (RCK1/2) domains, inhibits BK channel open-state probability. This PKC-dependent inhibition depends on a preceding phosphorylation of S1151 in the C terminus of the channel α-subunit. Phosphorylation of only one α-subunit at S1151 and S695 within the tetrameric pore is sufficient to inhibit BK channel activity. We further detected that protein phosphatase 1 is associated with the channel, constantly counteracting phosphorylation of S695. PKC phosphorylation at S1151 also influences stimulation of BK channel activity by protein kinase G (PKG) and protein kinase A (PKA). Though the S1151A mutant channel is activated by PKA only, the phosphorylation of S1151 by PKC renders the channel responsive to activation by PKG but prevents activation by PKA. Phosphorylation of S695 by PKC or introducing a phosphomimetic aspartate at this position (S695D) renders BK channels insensitive to the stimulatory effect of PKG or PKA. Therefore, our findings suggest a very dynamic regulation of the channel by the local PKC activity. It is shown that this complex regulation is not only effective in recombinant channels but also in native BK channels from tracheal smooth muscle.
Gesehen am 09.02.2024